EDUCATION IN THE PRIMARY AND PRE-PRIMARY SCHOOL IN THE CONTEXT OF THE SUSTAINABLE DEVELOPMENT - HRDLIČKOVÁ, Vlasta (Trends in education, 2010)
The paper deals with basic requirements concerning the education for sustainable development of the pre-school and young school children. The pre-gradual training of the preprimary and primary education of the future teachers is described in the article as well.
Keywords: education for the sustainable development; pre-primary education; primary education; pre-gradual training of the future teachers.